2007
DOI: 10.1021/la700377y
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Alkylated Polyethylenimines on the Formation of Gold Nanoplates

Abstract: Mono-and dialkylated polyethylenimines (PEI-1R and PEI-2R) were used for the facile synthesis of gold nanoplates with a preferential growth direction along the Au (111) plane. It was found that polymer hydrophobicity greatly influenced the nanoparticle morphology. PEI-1R in the acidic aqueous solution with a smaller degree of alkylation effectively adsorbed on the surface of gold nanoplates with the protonated ethylenimine groups rather than being aggregated in the bulk aqueous phase to form polymer aggregates… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(55 citation statements)
references
References 34 publications
1
54
0
Order By: Relevance
“…According to previous reports [32][33][34][35][36] and our findings presented here, we assumed that the large amount of tertiary amino groups in HBPO-star-PDEAEMA is significant for the preparation of AuNPs. To validate our assumption, we selected some hyperbranched polymers without amino groups as the controls, such as hyperbranched polyglycerol (HPG) and hyperbranched polyester H20, to prepare AuNPs through the same approach.…”
Section: Discussion Of Mechanisms For the Reduction Of Aunpssupporting
confidence: 76%
“…According to previous reports [32][33][34][35][36] and our findings presented here, we assumed that the large amount of tertiary amino groups in HBPO-star-PDEAEMA is significant for the preparation of AuNPs. To validate our assumption, we selected some hyperbranched polymers without amino groups as the controls, such as hyperbranched polyglycerol (HPG) and hyperbranched polyester H20, to prepare AuNPs through the same approach.…”
Section: Discussion Of Mechanisms For the Reduction Of Aunpssupporting
confidence: 76%
“…On the other hand, it has been recently demonstrated that colloidally stable gold nanoparticles can be conveniently prepared in as ingle step withouta ny external reducing agents by designing certain copolymers that can act as both ar educing agent and as tabilizer simultaneously.P olymers such as polymethylhydrosiloxane, [13] poly(N-vinyl-2-pyrrolidone), [14] poly(sodium acrylate), [15] poly(ethylene oxide), [16] polyallylamine, [17] poly [2-(N,N-dimethylamino)ethyl methacrylate], [18] and polyethylenimine [19] -based homopolymers or copolymers can fulfill the required dual role of reducing AuCl 4 À counterions to zerovalent gold and at the same time stabilizing the resulting gold nanoparticles. However,i ns yntheses with these polymers, large gold nanoparticles (> 3nm) were usually produced.…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis procedure followed a previously described procedure (Chen et al 2007). Two grams of PEI was suspended in dry methanol (25 mL), followed by the drop-wise addition of 1,2-epoxydodecane with continuous stirring under a nitrogen atmosphere at 60 °C for 12 h. After the solvent was removed by a rotary evaporator, the viscous solution was poured into hexane to precipitate the polymer.…”
Section: Synthesis Of Alkyl-grafted Peimentioning
confidence: 99%
“…The peak at 1650 cm -1 is representative of a deformation vibration of an N-H bond and it is split into two peaks and shifted to a long wavelength because of the substitution reaction of a primary amine. The C-H deformation vibration adsorption peak of methyl appeared at 1365 cm -1 (Nimesh et al 2007;Chen et al 2007). Figure 3 shows the 1 H NMR spectra of non-modified PEI, PEI-Ac, and PEI-Ed in CD 3 OD.…”
Section: Pei-acmentioning
confidence: 99%